Can the Poor Be Mobilized? Cooperation and Public Goods in Rural India - Anders Olofsgård; Shareen Joshi; Raj M. Desai (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
High coordination costs are often blamed for the low quality of public goods available to the poor. Participatory development programs have sought to lower these costs by improving trust and cooperation, but the evidence of their impact is mixed. We examine financial "self-help" groups in one of the poorest districts in India, using a unique combination of a village-randomized controlled trial and a lab-in-the-field experiment. A survey of 1,600 women before and after the intervention shows that the presence of these groups improved access to, and quality of, a critical local public good: water. Public goods games played with 184 participants in a subset of control and treatment villages indicate that cooperative norms are stronger where self-help groups were present. We find little evidence that membership leads to a convergence of tastes among group members. These results suggest that, in contrast to traditional community initiatives, self-help groups can build durable social capital in poor communities.
Keywords: F63; J16; O12; O17; 330; self-help groups; RCT; lab-in-the-field; public goods games; India